Serum levels of interleukin-6 are not dependent on the kidney function - L. Nässberger (Mediators of Inflammation)
Interleukin-6, also named B-cell stimulatory factor, is a glycoprotein with a molecular weight of 26 kDa. Increased serum levels of interleukin-6 (IL-6) are found in several disease conditions. We investigated the importance of a deteriorated kidney function upon IL-6 serum concentrations. No relation was found between serum levels of IL-6 and s-creatinine, r = 0.004. On the other hand, the serum concentration of complement protein factor D and soluble IL-2 receptor showed a good correlation to s-creatinine, r = 0.92 and 0.79, respectively. In conclusion, serum levels of IL-6 are not dependent upon a reduced kidney function.